Implementation of Joyfull Learning for Deep Learning in Indonesian Language Lessons - Maknun, Lu'luil; Niswar, Amda (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research aims to explore and formulate a conceptual framework for integrating the concept of joyful learning in the framework of deep learning in Indonesian learning in elementary schools. The main focus is to identify pedagogical strategies that are able to increase motivation, conceptual understanding, and emotional involvement of students. Method: The literature study was conducted by collecting reputable international literature published in 2020–2025 from the Scopus, Web of Science, ERIC, and Google Scholar databases. Documents that meet the criteria (discussion of joyful learning, deep learning, and elementary school context) are analyzed using content analysis and thematic analysis. Library data is grouped into main themes game based learning, storytelling, project collaboration, art activities, and structured reflection and mapped to three pillars of deep learning: mindful, meaningful, and joyful. Results: The results of the study revealed five implementation strategies. Gamification and language games have been shown to be most effective at spurring intrinsic motivation and active participation; storytelling and creative writing projects improve vocabulary retention; project collaboration strengthens social-emotional skills and critical thinking; art activities reduce language anxiety; and structured reflection develops metacognitive awareness. The mapping showed a balance between cognitive and affective aspects, with success indicators in the form of increased quiz scores (>20%), vocabulary retention (+40%), and the quality of metacognitive journals (rubric ≥80/100) Novelty: This research presents an adaptive joyful deep learning pedagogical blueprint for primary schools in Indonesia an integrated model that combines concrete activities, assessment indicators, and practical recommendations for curriculum, teacher training, and resource procurement thus making an original contribution to the international literature on humanistic and sustainable language learning.